Facilitating the scaling of climate-smart technologies and innovations in rice value chains in West Africa - Kpadonou, G. Esaïe; Ganyo, Komla Kyky; Segnon, Alcade Christel; Dossou-Yovo, Elliott Ronald; Ahouanton, Kokou; Lamien, Niéyidouba; Zougmore, Robert Bellarmin (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
As part of the synergies between AICCRA and the FSRP programs, a regional event was organized to facilitate the scaling of climate-smart technologies in rice value chains in West Africa. The workshop introduced FSRP stakeholders from seven countries to innovative climate-smart technologies for rice value chains and identified actionable steps to enhance the adoption and use of these technologies in FSRP countries.